Comparison of the low-dose oral therapy results with literature and parenteral therapy in children with vitamin B12 deficiency - Sarbay, Hakan; Akin, Mehmet (International Journal of Contemporary Pediatrics, 2022)
Background: It was aimed to investigate the results of vitamin B12 deficiency treatment with a lower vitamin B12 loading dose and compare with literature. Methods: Patients diagnosed with vitamin B12 deficiency at the pediatric hematology and oncology clinic between May 2017 and May 2018 were evaluated retrospectively. Patients who received a total of five doses of oral or parenteral cyanocobalamin treatment, 500 mcg two days a week in terms of region's socio-cultural status and accessibility to the health institution were included in the study. Vitamin B12 deficiency was defined as below 200 pg/ml. Post-treatment blood counts and vitamin B12 levels were reevaluated one month later after treatment was started. Vitamin B12 treatment responses were compared between the oral and parenteral groups and the results in the literature. Results: Parenteral cyanocobalamin was used in 134 patients and oral cyanocobalamin was used in 146 patients. Post-treatment vitamin B12 values at first month were investigated in 115 and 123 children in parenteral and oral arms, respectively. A total of 238 patients were included in the study. Although control mean±standard deviation (SD) vitamin B12 values increased significantly in both groups. Compared to the literature, vitamin B12 mean±SD values (oral treatment group 349.48±179.12, parenteral treatment group 486.77±52.77) after treatment did not differ significantly according to higher doses and longer treatment. Conclusions: In vitamin B12 deficiency, 500 mcg twice a week and a total of five dose oral cyanocobalamin is sufficient to increase the levels of vitamin B12.